Impact of laser land levelling on food production and farmers’ income: Evidence from drought prone semi-arid tropics in India - Pal, Barun Deb; Kapoor, Shreya; Saroj, Sunil; Jat, M. L.; Kumar, Yogesh; Anantha, K. H. (International Food Policy Research Institute, 2020)
Climate change has brought large instabilities in agricultural systems, in terms of both crop yield and net farm income. Climate smart agriculture is one of the innovative methods that tries to build resilience in agricultural systems. A study is conducted in Raichur district of Karnataka state in India to assess the impact of adoption of laser land levelling (LLL), a climate smart agriculture technology, on crop yield and farmers’ income. A primary survey was conducted in 2018 among 604 paddy growing farmers in Raichur district. The study provides results based on both qualitative and quantitative analysis of the data. The study examines farmers’ perceptions about climate change and effectiveness of LLL. Statistically, the results are evaluated using econometric methods like propensity score matching, coarsened exact matching, and endogenous switching regression. Advanced econometric methods are adopted to check for the problem of unobserved endogeneity. Adoption of laser land levelers increased crop yield by 0.5 tonnes/hectare and net farm income by Rs. 5000 per annum. Further, farmers observed drought as the most extreme climatic event which resulted in heavy crop loss to them. Lastly, farmers revealed that adoption of LLL reduced cost of cultivation and limits crop loss due to climate variability.